Editorial responsibilities arising from personalization algorithms. Issue 1 (2017) - Koene, Ansgar; Vallejos, Elvira Perez; Webb, Helena; Patel, Menisha; Ceppi, Sofia; Jurotka, Marina; McAuley, Derek
No abstract available